Pengaruh Augmented Reality (AR) dan E-WOM terhadap Purchase Decision Produk Bedak Wajah Wardah pada Official Store di TikTok Shop - Rismanto. H; Ramadhani. N; Sopiyanti. A; Anggraeni. M; Supriadi. S (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the influence of Augmented Reality (AR) and Electronic Word of Mouth (E-WOM) on purchasing decisions for Wardah face powder products at the official TikTok Shop. The research approach used a quantitative asosiatif method. Data were collected through an online questionnaire distributed to 96 respondents, with the sample size determined using the Slovin formula in an unknown population. The respondents were predominantly female, thus considered appropriate for the target market for cosmetic products, particularly facial makeup. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the relationships between the research variables. The results showed that Augmented Reality (X1) had no significant effect on purchasing decisions. Conversely, E-WOM (X2) had a significant and positive effect on purchasing decisions, indicating that consumer reviews and recommendations play a significant role in shaping consumer perceptions, trust, and purchase intention on digital platforms. The coefficient of determination value indicates that the research model is able to explain 35.3% of the variation in purchasing decisions, indicating that the contribution of AR and E-WOM is moderate. These findings imply that the success of digital marketing strategies in the cosmetics industry not only depends on the implementation of innovative technologies, but is also greatly influenced by the quality, intensity, and credibility of electronic communications between consumers.